1972
DOI: 10.1113/jphysiol.1972.sp009991
|View full text |Cite
|
Sign up to set email alerts
|

Electrical profiles in the corneal epithelium

Abstract: SUMMARY1. The potentials and resistances associated with the cell membranes of the rabbit corneal epithelium were studied with 3 M-KCl-filled microelectrodes.2. In the isolated cornea, the transepithelial potential was identical in polarity and magnitude to the simultaneously measured total cornea] potential. In contrast to previous findings, the stromal potential was positive to the tear side. Negative stromal potentials apparently derive from inadequate electrodes or method of penetration, and were not found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
2

Year Published

1973
1973
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(75 citation statements)
references
References 19 publications
(23 reference statements)
3
70
0
2
Order By: Relevance
“…At subepithelial stromal levels, the resistance to current flow was much lower, establishing only a very small lateral fields, wound site negative (Chiang et al, 1992). However, what has not been determined experimentally is the more relevant lateral fields immediately below the upper epithelial layer, where the tight junctons exist and across which the transcorneal PD is established (Klyce, 1972;Wolosin, 1988). Immediately below the migrating surface epithelia, cells are tightly packed, with little extracellular space.…”
Section: Physiological Significancementioning
confidence: 99%
“…At subepithelial stromal levels, the resistance to current flow was much lower, establishing only a very small lateral fields, wound site negative (Chiang et al, 1992). However, what has not been determined experimentally is the more relevant lateral fields immediately below the upper epithelial layer, where the tight junctons exist and across which the transcorneal PD is established (Klyce, 1972;Wolosin, 1988). Immediately below the migrating surface epithelia, cells are tightly packed, with little extracellular space.…”
Section: Physiological Significancementioning
confidence: 99%
“…Tight junctions between neighboring epithelial cells provide a highly resistant junctional barrier with corneal epithelial cells. The integrity of the tight junction is deeded for the corneal epithelial barrier function (Klyce, 1972). It has been demonstrated that corneal epithelial renewal is a continuous process, which is essential for wound healing in the cornea.…”
Section: Introductionmentioning
confidence: 99%
“…To examine the influence of low 02 tensions on epithelial and stromal thicknesses, corneas were mounted horizontally in a chamber developed previously for micro-electrode experiments (Klyce, 1972). The endothelial and epithelial surfaces were independently perfused with Ringer solution using syringe pumps (Razel,.…”
Section: Methodsmentioning
confidence: 99%